Auriculotherapy for insomnia in elderly people: a 6 week, double-blinded, randomised pilot study. (December 2017) - Suen, Lorna Kwai Ping; Molassiotis, Alex; Yeh, Chao Hsing; Yeung, Simon Kai Wang
Abstract: Background: Insomnia is a common disorder among elderly people. Sleep loss in the ageing population is associated with increased frequency of accidents and falls, poor health status, depression, and compromised quality of life (QoL). Auriculotherapy, a Chinese medicine-based approach, is a therapeutic method in which specific points in auricles are stimulated to achieve specific therapeutic purposes. In this randomised controlled pilot study, we aimed to determine preliminary treatments using magneto- auriculotherapy (MAT), laser auriculotherapy (LAT), or a combined auriculotherapy approach (ie, MAT plus LAT) to improve sleep and QoL in elderly people with insomnia. Methods: We included elderly people with insomnia as defined in the Diagnostic and Statistical Manual of Mental Disorders (5th edn). Participants were randomly allocated to three groups, as decided by a computer-generated randomised table: MAT only (placebo LAT followed by MAT; n=10); LAT only (LAT followed by placebo MAT, n=9); and combined AT (LAT followed by MAT, n=12). To achieve the effect of evaluator blinding, treatment effects were evaluated by a researcher who was not aware of types of treatment modality received by participants. Treatment was performed on one ear at a time on seven auricular points three times per week. Participants were assessed at baseline, after completion of the 6 week treatment course, and at 6 weeks follow-up. Outcome measures included: (1) Pittsburgh Sleep Quality Index (PSQI; score 0–21, with a score greater than 5 indicating poor sleep quality); (2) Insomnia Severity Index (score 0–28, high score indicates increased severity); (3) Patient Health Questionnaire (PHQ) to evaluate depressive condition (score 0–27, high score indicates depressive status); and (4) the Chinese (Hong Kong)-specific SF-12 v2 to determine QoL. This trial is registered atClinicalTrials.gov (numberNCT02970695 ). Ethical approval was sought from the Human Research Ethics Review Committee, The Hong Kong Polytechnic University (HSEARS20151129001). Findings: 31 participants aged 65 years or older were recruited from four community centres for elderly people in Hong Kong. Mean age of participants was 72·84 years (SD 5·01). A mixed between-participant and within-participant analysis of variance was conducted to assess the effects of three different interventions on different outcome variables across three time periods (pre-intervention, post-intervention, and 6 weeks follow-up). Substantial effects were observed for time, with all three groups showing a reduction in PSQI scores (F[2, 27]=13·53; p<0·0001; partial eta squared=0·501), sleep latency (F[2, 27]=13·53; p<0·0001; partial η 2 =0·751), level of insomnia severity (F[2, 27]=21·95; p<0·0001; partial η 2 =0·619), PHQ depressive score (F[2, 27]=10·53; p<0·0001; partial η 2 =0·438). Participants in all three groups showed an increase in sleep efficiency (F[2, 27]]=13·80; p<0·0001; partial η 2 =0·505), physical components of QoL (F[2, 27]=4·76; p =0·017; partial η 2 =0·261), and mental components of QoL (F[2, 27]=4·77; p=0·017; partial η 2 = 0.261) across three time periods. Comparison of the three types of intervention resulted in non-significant effects (p>0·05), suggesting absence of difference in effectiveness of the three treatment approaches. No adverse events were reported. Interpretation: The three treatment approaches using auriculotherapy improved sleep, depressive conditions, and QoL of participants. No difference was noted in treatment effects of these approaches. Future study with a large sample size should be conducted to establish causal relationship between these treatments and their effects. Funding: Health & Medical Research Fund (HMRF), Food and Health Bureau, Hong Kong Special Administrative Region, Hong Kong, China (13144061).